Maternal Healthcare to Migrants Immigrants Detained at the Heliport Facility in an Eastern Caribbean Nation - A Pilot Study - Dowlat, Cdr. Dr. Israel Kevin; Frontin, Kimerlene; Naraynsingh, Vijay; Islam MBBS,DM,FACS,FASBrS,FCCS, Shariful (Innovative Journal of Medical and Health Sciences, 2023)
Access to and the provision of adequate maternal healthcare services to any pregnant woman is a fundamental right championed not only by the World Health Organisation (WHO) but also by governments throughout the world. The provision of these services however becomes even more critical to immigrants and refugees who have left their homeland for political, economic, or social reasons. This is a unique situation in a developing country like ours with no past experience. The aim of this study is to examine the reason for the establishment of maternal services and to assess the quality of maternal healthcare services provided by the medical department of the Trinidad and Tobago Defence Force to the immigrant women detained at the Heliport Facility, Chaguaramas. This study also aims to identify the various challenges that are encountered in managing these immigrants, especially the pregnant women i.e. identification and training of appropriately skilled staff, the acquisition of specialized equipment, the identification of pregnant immigrants, and special accommodation for these individuals, access to antenatal and postnatal care by pregnant immigrants both internally and externally, and the management of unique challenges as communication and language barriers, and cultural practices which may impact the delivery of healthcare services to immigrants. We would like to share our unique experiences with the rest of the world and how the medical services of the Trinidad and Tobago Defence Force have attempted to overcome these challenges and improve the quality of maternal healthcare services provided to immigrants detained and managed at the Heliport Facility.